An Assessment of the Correlations between Marital Adjustment and Marital Satisfaction based on Light Triad Traits and Quality of Life in Women - Abdullah Azhdari; Eghbal Zarei; Kourosh Mohammadi (Women’s Health Bulletin, 2024)
Background: Light triad traits play a significant role in predicting one’s mental well-being and can greatly influence interpersonal relationships and overall happiness. This study aimed to assess the correlation between marital adjustment, marital satisfaction and quality of life in alignment with light triad traits.Methods: Structural equation modeling was used for data analysis. The study population included women living in Bastak, Iran in 2023. A total of 270 participants were selected through convenience sampling method, and completed Light Triad Scale, Dyadic Adjustment Scale (DAS), ENRICH Marital Satisfaction Scale (EMSS), and WHO Quality of Life-BREF questionnaires. Data were analyzed using SPSS version 26 and Amos version 24, with both descriptive and inferential analysis conducted through canonical correlation, regression analysis, and structural model testing.Results: There was a significant and positive relationship between clear personality traits and compatibility in married couples (β=0.564, P<0.001). Furthermore, the association between adaptation in married couples and quality of life (β=0.307) was also statistically significant at the P<0.001 level. Similarly, the association between marital satisfaction in married couples and clear personality traits (β=0.586) was statistically significant (P<0.001). Also, the association between marital satisfaction in married couples and quality of life was both positive and significant (β=0.215, P<0.001).Conclusions: Women’s marital satisfaction model, which is based on positive personality traits, highlights the significance of taking into account personality traits and their alignment when examining satisfaction in relationships. This suggests that partners with well-adjusted personality traits and compatible differences can contribute to higher levels of satisfaction within a marriage.